Calling All Actors: A holistic framework for tackling supply-side proliferation - Christopher Hobbs; Elisabeth Young (International Journal of Nuclear Security, 2015)
This article proposes a new holistic framework for tackling supply-side proliferation, based on a mix of punishments, incentives, and new normative standards (PIN) that could be taken by industry. After outlining a brief history of illicit nuclear trade, highlighting the increasingly sophisticated strategies adopted by proliferators, we explore in detail the PIN framework. We argue that to meet this challenge, industry must adopt behavior that goes beyond compliance with current regulations, particularly in the area of due diligence and information sharing.
Keywords: non-proliferation; supply-side; A.Q. Khan; illicit procurement; UNSCR 1540; beyond-compliance; corporate social responsibility